Răspuns :
[tex]\it (3x+2)^2 =4 \Leftrightarrow (3x+2)^2 - 4 = 0 \Leftrightarrow (3x+2)^2 - 2^2 = 0[/tex]
[tex]\it \Leftrightarrow (3x+2-2)(3x+2+2)=0 \Leftrightarrow 3x(3x+4) = 0 \Leftrightarrow [/tex]
[tex]\it 3x+4=0 \Leftrightarrow x =-\dfrac{4}{3}[/tex]
[tex]\it 3x =0 \Leftrightarrow x =0[/tex]
Ecuația admite două soluții : x = - 4/3 și x = 0.
[tex]\it \Leftrightarrow (3x+2-2)(3x+2+2)=0 \Leftrightarrow 3x(3x+4) = 0 \Leftrightarrow [/tex]
[tex]\it 3x+4=0 \Leftrightarrow x =-\dfrac{4}{3}[/tex]
[tex]\it 3x =0 \Leftrightarrow x =0[/tex]
Ecuația admite două soluții : x = - 4/3 și x = 0.
Ai doua metode : aplici (a+b)²=a²+2ab+b²
(3x+2)²=4
9x²+12x+4=4
9x²+12x=4-4
9x²+12x=0
3x(3x+4)=0
x₁=0; x₂= - 4/3
Sau aplici a²-b²= (a+b)(a-b):
(3x+2)²=4
(3x+2)²- 4=0
(3x+2+2)(3x+2-2)=0
(3x+4)*3x=0
x₁=0
x₂= - 4/3
Cu ocazia aceasta iti aduci aminte de formule! :)
(3x+2)²=4
9x²+12x+4=4
9x²+12x=4-4
9x²+12x=0
3x(3x+4)=0
x₁=0; x₂= - 4/3
Sau aplici a²-b²= (a+b)(a-b):
(3x+2)²=4
(3x+2)²- 4=0
(3x+2+2)(3x+2-2)=0
(3x+4)*3x=0
x₁=0
x₂= - 4/3
Cu ocazia aceasta iti aduci aminte de formule! :)